Role of Chemosynthetic Thermophilic Communities on the Biogeochemical Cycles of Minerals in the Orca Seamount Area, Antarctica - Blamey-Alegria, J (Taylor and Francis Ltd., 2021)
The Orca Seamount is a submarine volcanic structure, located in a tectonic area of the Bransfield Strait, characterized by cortical extension and roll back-type subduction. Recent investigations have described the presence of hydrothermal activity and thermophilic microorganisms in this submarine volcano, raising questions regarding the role these microorganisms might play in the environment. The presence of hydrothermal activity interacting with cold Antarctic marine waters has probably exerted a great impact on the chemistry of the Orca Seamount area, providing different types of substrates capable to support complex microbial communities. In this work, we further study the Orca Seamount area with respect to the mineralogy present in this environment and the role microorganisms might play in the biogeochemical cycles. Here we show that the assemblage of minerals detected in the Orca Seamount area is like those commonly found in other hydrothermal environments, consistent with previous investigations reporting hydrothermal activity in this zone. Sulfur- and iron-bearing minerals in addition to inorganic soluble compounds are able to support chemosynthetic microbial communities inhabiting the Orca Seamount. The role of these microorganisms on the sulfur, iron, and carbon cycle is discussed and analyzed in the context of the mineralogy and conditions of the environment. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Biogeochemical cycles; Bransfield Strait; deep-sea biosphere; mineral metabolism